Symmetric dimethyl arginine and N-acetyl-β-D-glucosaminidase lysozimuria of proximal renal tubules as a target for nephrotoxicity in patients with rheumatoid arthritis treated with disease modifying antirheumatic drugs - Dejan Spasovski; Arif Latifi; Nada Marina; Jordan Calovski; Irena Kafedziska; Gjorgi Božinovski; Snežana Percinkova; Maja Slaninka-Micevska; Trajan Balkanov; Beti Dejanova; Sonja Alabakovska; Svetlana Krstevska-Balkanov; et al. (Society of Diabetic Nephropathy Prevention, 2013)
Background: The aim of this study was to determine the effect of initial therapy with some disease modifying antirheumatic drugs (DMARDs) (Methotrexate and Ketoprofen) on glomerular and tubular integrity in patients with Rheumatoid arthritis (RA). Objectives: To determine whether there is a change in clinical and laboratory indicators of renal function in course of the follow up of treatment and whether that change correlates with the dynamics of the quantity of enzymes excreted in urine and reactants of the acute phase. Materials and Methods: Using colorimetric method for determination of NAG, samples of 70 participants were examined (35 RA patients treated with Ketoprofen only, 35 RA patients treated with combined use of Methotrexate and Ketoprofen). The follow up was 5 time-intervals in the course of 24 weeks. Results: There was moderate correlation between NAG and microalbuminuria (r=0,34) in the group of patients treated with Ketoprofen only, while statistically significant correlation (r=0,21) was seen in group of patients with combined use of Methotrexate and Ketoprofen. NAG enzymuria in size, number of patients registered, and time of appearance were greater and appears earlier in the group with the combined use of Methotrexate and Ketoprofen compared with the mono-therapy with Ketoprofen. Mean urinary NAG induction was increasing with the concomitant use of Methotrexate and Ketoprofen. Conclusions: Methotrexate is more potent NAG inductor than Ketoprofen and provokes greater tubular enzymuria than Ketoprofen.